Cross-sectional shape design of automobile structure considering rigidity and driver's field of view. (January 2018) - Zuo, Wenjie; Lu, Yayun; Zhao, Xing; Bai, Jiantao
Highlights: Cross-sectional rigidity and driver's field of view are both considered to design automobile A-pillar structure. Torsional moment of inertia for five types of cross-sectional cells is entirely formulated. Calculation of obstruction angle is innovatively expressed as a nonlinear optimization problem. CarFrame engineering software is developed to guide the conceptual design of automobile structure. Abstract: Thin-walled beam structure can be used to efficiently predict the performances of automobile frame for conceptual design. However, it is an open issue to acquire an accurate cross-sectional shape of A-pillar structure considering both rigidity and driver's field of view (DFOV). This paper proposes an approach to calculate the cross-sectional rigidity and DFOV. Firstly, formulations of cross-sectional properties, including open, single-cell, double-cell, three-cell, four-cell section, are summarized. Secondly, the obstruction angle is introduced to describe DFOV, which is acquired by a nonlinear optimization model. Finally, a A-pillar example of Toyota RAV4, solved by the developed software – CarFrame, proves that the proposed method can be completely applied at the conceptual design of the automobile structure.